2019
DOI: 10.3390/cells8121526
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Macrophages in Hematologic Malignancies: New Insights and Targeted Therapies

Abstract: The growth of hematologic malignant cells can be facilitated by other non-tumor cells within the same microenvironment, including stromal, vascular, immune and mesenchymal stem cells. Macrophages are an integral part of the human innate immune system and the tumor microenvironment. Complex interplays between the malignant hematologic cells and the infiltrating macrophages promote the formation of leukemia, lymphoma or myeloma-associated macrophages. These pro-tumorigenic macrophages in turn play an important p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 99 publications
0
40
0
Order By: Relevance
“…Mesenchymal stem cells (MSCs) are cells with the ability to differentiate into structural lineages (osteoblasts, adipocytes and chondrocytes) and have been isolated from a wide variety of organs and tissues [48]. Bone marrow-derived MSCs are recruited to the TME, providing the CSC niche with a combination of secreted cytokines that modulate the stroma [49], the immune system [50] and the MSCs themselves [51]. This facilitates CSC maintenance, but also chemoresistance within the TME [52].…”
Section: The Csc Niche the Tumor Microenvironment And Metastasismentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are cells with the ability to differentiate into structural lineages (osteoblasts, adipocytes and chondrocytes) and have been isolated from a wide variety of organs and tissues [48]. Bone marrow-derived MSCs are recruited to the TME, providing the CSC niche with a combination of secreted cytokines that modulate the stroma [49], the immune system [50] and the MSCs themselves [51]. This facilitates CSC maintenance, but also chemoresistance within the TME [52].…”
Section: The Csc Niche the Tumor Microenvironment And Metastasismentioning
confidence: 99%
“…Recent studies have found that M2-like macrophages, called tumor-associated macrophages (TAMs), were involved in promoting tumor progression and metastasis by boosting angiogenesis, stimulating tumor cells' proliferation, migration and invasion [27][28][29] . Although TAMs are initially considered to affect solid tumors, they are later found to predict poor outcomes in blood diseases such as lymphoma, leukemia and multiple myeloma [30] . But the roles of TAMs in MDS patients have not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, “alternatively activated” or M2 macrophages, in which tumor-associated macrophages (TAMs) are included, play an immunosuppressive role that facilitates tumor progression and are characterized by high expression levels of scavenging (CD163) and mannose (CD206) receptors, arginase and the production of IL-10, VEGF and matrix metalloproteinases (MMP). The M1/M2 polarization depends on the activation signaling present in the environment: Th1-derived cytokines such as interferon-γ (IFN-γ) and bacterial products, including bacterial lipopolysaccharides (LPS), promote M1 differentiation, whereas Th2-derived cytokines like IL-10 and glucocorticoid hormones drive the differentiation of macrophages towards an M2 phenotype [ 136 , 137 ]. In MM, it has been reported that both tumor cells and BM mesenchymal stromal cells produce chemokines such as CXCL12, CCL2, CCL3, and CCL14 that promote macrophage migration to the tumor niche and polarize macrophages towards an M2-like phenotype in vitro ( Figure 2 ) [ 138 , 139 , 140 ].…”
Section: Myeloid Cells Involved In MM Progressionmentioning
confidence: 99%